Pivot to persevere: Temporary pivots as a~response to exogenous shocks - Clara Scheve; Markus Reihlen; Thomas Gegenhuber (Schmalenbach Journal of Business Research (SBUR), 2024)
Despite much progress in the research on pivots as a~response to crisis, the nature of temporary pivots remains unclear. This article investigates how a~venture responded to the challenges of the COVID-19 pandemic by performing a~temporary pivot. Drawing on an inductive, longitudinal case study of the fast-growing young venture "Gazelle," we developed a~process model of temporary pivots that encompasses three phases: what evokes a~temporary pivot; how it is enacted; and what effects it has on the venture. Our findings suggest that temporary pivots require effectual decision-making and the reversibility of changes made. Our research contributes to the growing literature on pivoting by conceptualizing the temporary pivot as a~short-term entrepreneurial response to exogenous shocks and part of a~long-term strategy of perseverance.
Keywords: 650; Crisis response; Exogenous shock; Exploratory perseverance; Temporary pivot